Tracking Microplastics in the Air: Cutting-edge Methods for Indoor and Outdoor Environments - Khadija Sharaf Din; Muhammad Fahim Khokhar; Hira Amjad (Aerosol and Air Quality Research)
Abstract The scarcity of research work on airborne microplastics may be attributed to a lack of rigorous methodology since studying the microscopic realm of air quality is challenging. Previous studies on airborne microplastics have shown disparate approaches for exploring airborne MPs with little methodological coherence, limiting the comparability of results. This study aims to provide a rigorous methodology to quantify and characterize airborne MPs more precisely. The first step is efficiently separating particulate matter (PM2.5, PM10) from Whatman® quartz filter paper using sonication to recover all the samples. Sample treatment begins with organic matter (OM) removal from sample particles by oxidative digestion using hydrogen peroxide (H2O2) (15%) at 70°C (for 1 hour) which is highly efficient and saves time as it would otherwise take 7–8 days at room temperature. Zinc chloride (ZnCl2, 1.6 g cm−3) has been used in density separation of polymers owing to its high efficiency and reusability. It has been demonstrated that ZnCl2 and H2O2 have no negative impacts on sample particles under the given conditions. This method has been proven suitable for environmental samples and can be reproduced within 2 days.